2018
DOI: 10.3389/fphar.2018.00868
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Mast Cell Protease 4 Deletion Protects Heart Function and Survival After Permanent Myocardial Infarction

Abstract: Chymase, a mast cell serine protease involved in the generation of multiple cardiovascular factors, such as angiotensin II and endothelin-1 (ET-1), is elevated and participates in tissue degeneration after permanent myocardial infarction (PMI). Anesthetized 4-month old male wild-type (WT) C57BL/6J mice and mouse mast cell protease-4 knockout (mMCP-4 KO) congeners were subjected to ligation of the left anterior descending (LAD) coronary artery. A group of mice was then subjected to Kaplan-Meier 28-day survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…More recently, Pinke et al (2020) showed that mast cell stabilization with ketotifen lowered disease prevalence and severity and the expression of chymase and carboxypeptidase A in mice, thus supporting a potentially therapeutic indication for mast cell stabilizers in multiple sclerosis (Pinke et al, 2020). Deleterious roles for mast cell-derived chymase have also been shown in experimental models of cardiac infarct, ischemia/reperfusion, and atherosclerosis (Jin, 2003;Tejada et al, 2016;Houde et al, 2018). Finally, patients with myocardial infarction show increased levels of plasmatic and cardiac and chymase activity in the same organ (Oka et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…More recently, Pinke et al (2020) showed that mast cell stabilization with ketotifen lowered disease prevalence and severity and the expression of chymase and carboxypeptidase A in mice, thus supporting a potentially therapeutic indication for mast cell stabilizers in multiple sclerosis (Pinke et al, 2020). Deleterious roles for mast cell-derived chymase have also been shown in experimental models of cardiac infarct, ischemia/reperfusion, and atherosclerosis (Jin, 2003;Tejada et al, 2016;Houde et al, 2018). Finally, patients with myocardial infarction show increased levels of plasmatic and cardiac and chymase activity in the same organ (Oka et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…We, however, could not detect a signal of active caspase-3 in these early time frames. Published literature suggests that this staining is rather feasible at 72 h of permanent LAD ligation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…mMCP4 was extensively expressed in MCs post MI, and the deficiency of mMCP4 played a protective role in murine cardiac function after coronary artery ligation, which was characterized by reduced CM apoptosis, reduced accumulation of immune cells, impaired TGF-β signaling, enhanced ECM degradation, and amelioration of the ejection fraction [126]. Similarly, another finding demonstrated that in mMCP-4 knockout mice, the size of the infarcted area, ventricular remodeling, and apoptotic signaling were prominently reduced compared to those in the WT congeners [127]. Insulin-like growth factor-1 (IGF-1), a protective polypeptide, was degraded by mMCP4.…”
Section: Recent Findings Regarding Mcs In Cardiac Remodelingmentioning
confidence: 95%